Novel drugs for the treatment of chronic pruritus. (2nd December 2018) - Pereira, Manuel P.; Ständer, Sonja
ABSTRACT: Introduction : Chronic pruritus (CP) is a multidimensional condition severely affecting the quality of life of those affected. Although a multitude of topical and systemic agents are recommended for CP of different origins, the condition often remains refractory to treatment. However, a deeper understanding of the pathophysiology of CP is leading to the development of novel antipruritic drugs. Areas covered : This paper reviews antipruritic therapies in development by gathering data from recently published articles and clinical trials databases. Interleukin-31 antibodies and other biologics, neurokinin-1 receptor antagonists, opioid-receptor agonists/antagonists, TrkA-antagonists, and ileal bile acid transporter inhibitors are discussed. Expert opinion : Clinical trials have rendered promising data on the antipruritic efficacy and safety of novel drugs, but further studies are necessary to enhance our understanding of the different conditions associated with CP. High-quality clinical trial data is necessary for these agents to be approved for the treatment. Basic research should be intensified to identify pathways relevant for CP and to further the development of new specific antipruritic drugs.